2374. Genomic Characteristics of Recurrent Staphylococcus aureus Skin and Soft-Tissue Infection Among US Army Trainees. (26th November 2018) - Verratti, Kathleen; Player, Robert; Wood, Shannon; Schlett, Carey; Elassal, Emad; Forsyth, Ellen; Ellis, Michael; Tribble, David R; Millar, Eugene; Bennett, Jason
Abstract: Background: Skin and soft-tissue infections (SSTI) are common among military recruits, and some experience recurrent SSTI (two infections ≥30 days apart) during training. We used whole-genome sequencing (WGS) to assess the relatedness of strains from recurrent S. aureus SSTI cases and their close contacts. Methods: From 2010 to 2014, we prospectively identified SSTI cases among US Army Infantry trainees (Fort Benning, GA), obtaining infection swabs at the time of presentation for all SSTIs and multiple anatomic site colonization swabs at the time of presentation for the first infection. Thereafter, we selected cases of recurrent S. aureus SSTI with phenotypically concordant paired isolates (e.g., MRSA-MRSA). We also selected concordant colonization isolates from recurrent cases as well as concordant infection isolates from SSTI cases in the same training class as the recurrent case. Isolates were characterized by WGS. The number of single nucleotide polymorphism (SNP) differences between isolates was calculated. Phylogenetic trees were constructed to identify patterns of intra- vs. extra-host S. aureus acquisition among cases of recurrent infection. Results: We identified 23 cases of recurrent S. aureus SSTI with concordant infection isolates (18 MRSA). The median (range) pairwise SNP difference for intrahost infection isolates was 15 (0–3, 768); 12 (0–348), MRSA and 310 (3–3, 768), MSSA. Nine (39%) were colonized with a concordant strain (5 MRSA), yielding 14 colonization isolates (7 MRSA). The median pairwise SNP difference between intrahost colonization and recurrent infection isolates was 57 (2–3, 582); 5 (2–3, 582), MRSA and 167 (2–313), MSSA. Infection isolates from 33 proximal cases (27 MRSA) were identified. The median pairwise SNP difference between recurrent infection isolates and that of a proximal case was 24 (1–531); 20 (1–216), MRSA and 307 (286–531), MSSA. Variant analysis showed no difference between the number of putative high impact SNPs between infection (μ = 11, σ = 20) and colonization (μ = 19, σ = 42) isolates. Conclusion: WGS of S. aureus from recurrent SSTI suggests patterns of intra-host reinfection as well as intra-host acquisition/infection. Targeted decolonization may prevent recurrent S. aureus SSTI. Disclosures: All authors: No reported disclosures.